Cooperation's Cost - Baer, Miriam Hechler (2011)
This Article explores the costs and benefits of criminal cooperation, the widespread practice by which prosecutors offer criminal defendants the opportunity to receive reduced sentences in exchange for their assistance in apprehending other criminals. On one hand, cooperation increases the likelihood that criminals will be detected and prosecuted successfully. This is the “Detection Effect” of cooperation, and it has long been cited as the policy’s primary justification. On the other hand, cooperation also reduces the expected sanction for offenders who believe they can cooperate if caught. This is the “Sanction Effect” of cooperation, and it may grow substantially if the government enlists too many cooperators, enables them to be sentenced too generously, or causes them to become overly optimistic about their chances of receiving a cooperation agreement. When the government allows the Sanction Effect to grow too large, it undermines one of its key tools for improving deterrence. Indeed, when the Sanction Effect outweighs the Detection Effect, cooperation reduces deterrence, and the government unwittingly encourages more crime. Since cooperation is itself administratively costly, the policy perversely causes society to pay for additional crime. This Article reorients the cooperation debate around the fundamental question of whether cooperation deters wrongdoing. Drawing on economics and behavioral psychology, it provides a framework for better understanding how and when cooperation works. Government actors who laud and rely on cooperation must address the fundamental question of whether it actually deters wrongdoing. To do otherwise is to leave society vulnerable to cooperation’s greatest cost